Mathematics a very short introduction - Gowers Timothy (Oxford OUP, 2002)
This book is to explain the differences between advanced, research-level mathematics, and the sort of mathematics we learn at school. The most fundamental differences are philosophical, and readers of this book will emerge with a clearer understanding of
Keywords: Mathematics